Independent States: A Perspective from International Relations - Murillo-Zamora, Carlos (2021)
According to the nature of the Westphalian system, the independent state is the central actor in international relations; however, the discipline has not developed theoretical approaches regarding the independence process which is considered more a concern of the international law and the political interests of state actors. Then, in this article, the issue of independence is analyzed as a basic step for political entities to access the statehood becoming this a basis for understanding the role of the independent State in the Westphalian order. Acknowledging the existence of deep changes in the international system, it is necessary to observe the variations in the conception of independence, especially regarding self-determination and recognition principle. This principle has greater relevance since the 1990s due to the disintegration processes of some countries, being Kosovo one of the main cases. Taiwan is also a relevant experience. Another key point is the weakening process of the state, with the appearance of variants that question the status and existence of the state actor. At the end of this paper, a brief reference is made to the Latin and Central American experience, which show particularities since the 19th century.